Aspek Hukum Perlindungan Indikasi Geografis Berbasis Ham - Maria Alfons (Jatiswara, 2015)
Law No. 15 of 2001 Trademarkare manage geographical indication on articles 56 to 58 as part of the substance of geographical indications (GI) basically regulate the protection of the products to local communities as a sign that indicates the place of origin of goods is due to human factors, or a combination of both factors, provide specific characteristics and quality of the goods results of the product. Then, the issuance of Government Regulation No. 51 year 2007 on Geographical indications for clearer protect as expected in the TRIPS Regalements. Constitutionally Article 33, paragraph 3 of the 1945 Constitution mentions "The land, the waters and the natural resources within shall be under the powers of the State and shall be used to the greatest benefit of the people". It means that the people are given the opportunity to manage and exploit the natural resources for the people's welfare. This is the shape of the state which provides the opportunity for people to explore the potential of natural resources to be managed and used as the economic value it is then used and worn as the property of the citizen, and then it became attachedas a fundamental right that cannot be separated from the ownership of the wealth of human rights.